Assessment of Knowledge, Attitudes and Practices of Food Safety among Food Handlers at Cafeterias in UTHM Pagoh Campus - moly, Khani; Rahim Jamian (Progress in Engineering Application and Technology, 2024)
Food handlers are crucial in the food service industry, responsible for ensuring the safety and quality of food products. Poor hygiene and faulty practices are the leading cause of foodborne diseases. This study aimed to assess the knowledge, attitudes, and practices (KAP) of food handlers at cafeterias in Universiti Tun Hussein Onn Malaysia (UTHM) regarding food safety and hygiene. Data was collected through questionnaire distribution and analyzed using statistical data analysis software. The findings are expected to provide valuable insights into the interaction between prevailing food safety beliefs, knowledge, and practices of food handlers to minimize foodborne outbreaks in a university environment.